Cross-Cultural Differences and Similarities in the Expression of Jealousy in a Couple: A Comparative Study Between Couples of Greek and Albanian Descent - Despina Sikelianou , Dr. (International Journal of Psychosocial Rehabilitation, 2015)
This research is a comparative study whose aim was to investigate the cross-cultural differences and similarities in the ex- pression of jealousy between Greek couples and couples of Albanian descent who live in Greece. In this study, the survey method was used and the research was quantitative. The research process lasted a total of three (3) months (May-August 2011) and was conducted in two (2) large urban centres in our country: Athens and Thessaloniki. According to the results of the research: i) the two major reasons causing jealousy in a couple in both population groups is sexual intercourse with another person and the emotional attachment of either partner to another person. Secondary reasons are a partner’s pursuit of their career and their spending more time with their friends ii) during a jealousy incident, couples of Albanian descent display mainly violent behavior towards their partner, in contrast to couples of Greek descent, where the partners either dis- tance themselves from each other or exercise control over/check up on one another, iii) couples of Albanian descent claim that going through the process a jealousy incident strengthens their relationship. In contrast, couples of Greek descent claim that such an incident is the reason they become estranged from their partner and distance themselves, and they usually react by ending communication with one another.